2018
DOI: 10.1186/s12877-018-0828-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between health risks and frailty in relation to the degree of housing damage among elderly survivors of the great East Japan earthquake

Abstract: BackgroundMany survivors of the Great East Japan Earthquake that occurred in 2011 were at risk of deteriorating health, especially elderly people living in disaster-stricken areas. The objectives of this prospective study were: a) to clarify the different lifestyle and psychosocial factors associated with frailty by sex among the non-disabled elderly survivors, and b) to describe the differences in characteristics stratified by the degree of disaster-related housing damage.MethodsWe followed 2261 Japanese surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 40 publications
2
33
1
Order By: Relevance
“…According to a report from Fukushima, few people started smoking after the disaster; the smoking rate was not high among victims in 2012 compared with smoking rate among the general population, and smoking rate decreased after the disaster [11]. A longitudinal study of elderly people in Iwate Prefecture from 2012 to 2015 found that smoking prevalence was higher among people with complete destroyed houses and that continued decreasing from 2011 through 2014 and increased in 2015 [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to a report from Fukushima, few people started smoking after the disaster; the smoking rate was not high among victims in 2012 compared with smoking rate among the general population, and smoking rate decreased after the disaster [11]. A longitudinal study of elderly people in Iwate Prefecture from 2012 to 2015 found that smoking prevalence was higher among people with complete destroyed houses and that continued decreasing from 2011 through 2014 and increased in 2015 [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, about 70% (561/792) of the participants who lived in PHs at 2 years after the GEJE continued residence in a PH at 4 years after the disaster. Possible reasons for the high rate of continued residence in a PH are economic poverty,5 lack of public housing or loss of motivation to move out 7…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that prolonged PH stays were associated with physical dysfunction and psychological distress 6 7 26. Ishii et al indicated that most PHs were built in areas that were separated from the local communities in which survivors previously lived, and did not include commercial areas; therefore, refugees tended to confine themselves to their own PHs, leading to physical inactivity,26 which is considered to be related to MSK pain 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review revealed psychological burdens such as a deterioration in mental health [21] and an increase in prevalence of post-traumatic stress disorder (PTSD) [22], as well as deterioration in health due to living in an evacuation center or a worse living environment [23], an increase in frailty risk [24], spread of pneumonia [25], and an increase in the number of people with subjective symptoms such as gastrointestinal and/or musculoskeletal symptoms [26].…”
Section: Factors Causing Increase In Long-term Care Certification Ratmentioning
confidence: 99%